EFFECT OF PROTEIN SUPPLEMENTATION ON THE PRODUCTIVITY OF TAGGAR GOATS UNDER DRY NATURAL GRAZING, WESTERN SUDAN - Bushara, Ibrahim; M.A. Abu Nikhaila, Abdel Moneim; M.Mekki, Dafalla (Journal of Veterinary Medicine and Animal Production, 2022)
The experiment was conducted in Taggar goats under natural grazing to evaluate the effect of two supplements varying in protein on some reproductive and productive traits. Forty seven mature Taggar goats were used in this experiment. Animals were allocated to three feeding regimes, group 2 (16.7% CP), group 3 (20.4 % CP) and group 1 (un-supplemented) in a complete randomizes design. Results indicated that supplemented does secured higher litter size of 1.5 and 1.33 in group 2 and group 3 respectively, compared with 1.2 in un-supplemented group(1). Where kidding rate was high in supplemented groups (100%) compared with un-supplemented group (93.8%). Body weight was heavier at time of kidding and weaning for supplemented does compared with un-supplemented does. The kidding interval for the supplemented does was shorter (247.81±8.38 and 242.60±7.88 days) for does in group 2 and 3 respectively compared with does in un-supplemented group (288.94±6.84 days). Similarly, the service period had been reduced in supplemented does compared with un-supplemented does, the respective values were 74.32±4.96, 83.46±4.67 and 93.08±4.22 days for group 2, 3 and 1 respectively. The results of milk component indicated that supplemented does recorded higher protein, lactose and total solid content whereby the fat content was higher in un-supplemented does. The supplementation which was given to does had reduced abortion and mortality rates compared with the un-supplemented does.